Good faith and change of circumstances as regulatory mechanisms before the fulfillment of Treaties (2017)
The stopell institution is perfectly known in continental doctrine as the theory of proper acts, which demonstrates fidelity to the pacta sunt servand principle; its nature as a general principle of law is autonomous and operates in the shadow of bilateral or multilateral negotiations whose support is based on mutual trust. Explaining how the obligations imposed by International Law on the States in a treaty can vary due to changed circumstances (rebus sic stantibus), without affecting the fulfillment of the object and purpose of the Treaty, nor creating obligations for third parties, constitutes the objective of this article, which from the methods, legal history, and synthesis analysis, demonstrates that the obligations imposed by the Charter of the United Nations prevail over the obligations contracted in another international agreement, in any circumstances, constituting respect for the norms ius cogens, a limit to the action of the State due to the change of circumstances.